Morphological types and arrangement of cone cells, and the visual acuity of sutchi catfish pangasianodon hypophthalmus - Nai, Han Tan; Mukai, Yukinori (Universiti Teknologi Malaysia, 2015)
This study was conducted to obtain fundamental understanding of the vision of adult sutchi catfish Pangasianodon hypophthalmus. The left eyes of sutchi catfish were removed, fixed in Bouin’s solution and were cut into 17 regions. The 17 regions were then immersed in an ethanol series, cleared with histolene, embedded in paraffin, cut into 6 μm thick tangential sections, and stained with haematoxylin-eosin. Only single cone cells, which were closely space, were identified from the stained sections. The area around the bottom region showed tendency of higher density of single cone cells.